2019
DOI: 10.1155/2019/9128273
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Takotsubo Syndrome and Acute Coronary Syndrome of the Right Coronary Artery

Abstract: Takotsubo syndrome (TTS) is an increasingly recognized heart disease that was initially regarded as a benign condition, but since has proven to cause irreversible myocardial damage, resembling that of acute coronary syndrome (ACS). The etiology of TTS is still uncertain but may be associated with catecholamine elevations during times of emotional or physical stress. Catecholamines are also understood to have prothrombotic properties, which could lead to ACS. With these similarities, differentiating these two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The third and rarest condition that may occur is acute coronary syndrome as a consequence of TTS [78]. As discussed later, this reciprocal cause-and-effect relationship between CAD and TTS is still under discussion.…”
Section: Coexistence Of Takotsubo and Coronary Artery Disease-coincid...mentioning
confidence: 99%
See 1 more Smart Citation
“…The third and rarest condition that may occur is acute coronary syndrome as a consequence of TTS [78]. As discussed later, this reciprocal cause-and-effect relationship between CAD and TTS is still under discussion.…”
Section: Coexistence Of Takotsubo and Coronary Artery Disease-coincid...mentioning
confidence: 99%
“…Lin and Young showed that the occurrence of cyclic blood flow decreases in the canine coronary arteries grew by 60% when the plasma epinephrine concentration was raised to about 27 nmol/L [91]. Given that catecholamines are known to have prothrombotic effects and that TTS is linked to an increase in catecholamines, it is plausible that TTS preceded ACS in certain case reports that have been documented in the literature [78]. Despite coronary artery thrombosis, SCAD, or LV systolic dysfunction as potential pathological mechanisms, ACS in this setting might sometimes be secondary to embolic events from a LV thrombus developed in the akinetic LV apex.…”
Section: Takotsubo Triggered By Ischemia-the Chicken-egg Paradoxmentioning
confidence: 99%
“…Clinically, it mimics an acute coronary syndrome (ACS), but coronaries are normal on cardiac catheterization. It is likely caused by excessive catecholamine stimulation although the exact etiology is still under discussion [ 3 , 5 , 6 ]. In the intraoperative setting, it can be triggered by the surgical condition, the surgical procedure, or the anesthesia itself [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress factors related to Takotsubo cardiomyopathy6,10,11,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] …”
mentioning
confidence: 99%